THE NATURE OF THE LYRICAL GENRE IN SATIRE: POETOLOGICALSTRUCTURAL INTEGRITY - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
THE NATURE OF THE LYRICAL GENRE IN SATIRE: POETOLOGICALSTRUCTURAL INTEGRITY